Non-governmental organizations as key partners in mental health in Europe - Baumann, A. E. (Die Psychiatrie, 2014)
The shift towards a rights-based approach to health which has taken place over the past decade has strengthened the role of civil society and their organizations in raising and claiming the entitlements of different social groups. It has become obvious that non-governmental organizations (NGOs) are central to any successful multi-stakeholder partnership, and they have become more recognized as key actors in health policy and programme development and implementation. There is a broad spectrum of NGOs active in the area of mental health in Europe which aim to empower people with mental health problems and their families, give them a voice in health policy development and implementation and in service design and delivery, to raise awareness and fight stigma and discrimination, and foster implementation of obligations set by internationally agreed mental health policy documents. With the endorsement of the Mental Health Action Plan 2013-2020 (20) and the European Mental Health Action Plan (19) stakeholders agree to strengthen capacity of service user and family advocacy groups and to secure their participation as partners in activities for mental health promotion, disorder prevention and improving mental health services.
Keywords: Civil society; non-governmental organizations; mental health